Reactivity of silicate liming materials from Northern Europe assessed by Soil Incubation and two pH Stat methods - Erstad, Karl-Jan; Konovalov, Nikolai Y.; Putro, Jukka; Rex, Martin; Luukkonen, Elsa (Agricultural Research Centre of Finland, 2000)
Silikaattisten kalkitusaineiden reaktiivisuutta tutkittiin norjalaisella ferromangaanikuonalla, kolmella ruotsalaisella ja kolmella suomalaisella masuuni- ja konvertterikuonalla. Vertailumateriaalina kokeissa oli kiteinen kalsiitti. Kolmea reaktiivisuuden määritysmenetelmää käytettiin kuonien luontaisen kalkitusvaikutuksen selvittämiseksi ja standardisoinnissa tarvittavien matemaattisten riippuvuuksien laskemiseksi. Astiakokeiden perusteella konvertterikuonat ja amorfiset masuunikuonat olivat kalsiittia tehokkaampia hietamaassa, kun taas happamassa turvemaassa kuonien ero kalsiittiin oli pienempi. Pitemmillä testausajoilla kuonat olivat fraktioittain tarkasteltuna lähes yhtä tehokkaita kuin kalsiitti. Joskus kalsiitti oli hieman tehokkaampi hienoissa raeluokissa, kun taas kuonat olivat ylivoimaisia karkeammissa raeluokissa

Reactivity studies were carried out with a range of particle size fractions using one Norwegian ferro manganese slag, three Swedish and three Finnish blast furnace and converter slags. Their effect on soil pH was compared with a crystalline calcite. Besides establishing the slags' inherent liming ability, three methods were used in order to establish mathematical relationships for the conversion of data according to European standardisation. With the Soil Incubation method it was found that the converter slags and the amorphous blast furnace slags were slightly superior to the other slags in raising the soil pH of a silty loam, whereas in an acid peat the differences were quite small. Over a prolonged period the slags showed almost the same efficiency as the calcite. When comparing the same particle size fractions, in some cases the finer fraction of calcite gave a better result, whereas the slags were often superior in the coarse particle sizes. Using Sauerbeck/Rietz and the modified Finnish pH Stat methods the converter slags and the amorphous slags showed the highest neutralizing ability. The Finnish method performed a more gentle acid-lime reaction, and this time-consuming method correlated better with reaction in soil than the Sauerbeck/Rietz method. Conversion factors between data from the three methods were computed for all particle size fractions, and correlation equations for practical use established.
Keywords: kalkitusaineet; astiakokeet; menetelmät; pH; maaperä; calcite; fineness; liming materials; reactivity; slags; soil